THE INTEGRATION OF A BALANCED SCORECARD MODEL AND RISK MANAGEMENT ISO 31000:2018 TO IMPROVE SAVINGS AND LOANS COOPERATIVE’S PERFORMANCE - Agnes Dita Mayesti Tokede; Perminas Pangeran (Department of Management - Institut Shanti Bhuana, 2024)
This study aimed to integrate the Balanced Scorecard and enterprise risk management processes based on ISO 31000 at Pamona Timur Savings and Loans Cooperative (SLC). The data were obtained through questionnaires and in-depth interviews which were conducted with the Head of the Cooperative. This research was a case study research involving leaders in each stage of the ISO 31000-based risk assessment process, which includes how to identify, analyze, evaluate, and mitigate risks in the case of Pamona Timur Savings and Loans Cooperative. The identified risks consisted of four types of risk, namely: credit risk, liquidity risk, business risk, and operational risk. Based on the results of the risk assessment, the highest risks were credit risk and liquidity risk. These two risks require priority to be addressed immediately. The risk mitigation plan was expected could help to overcome the risks by determining the best risk treatment options that would provide added value to Pamona Timur Savings and Loans Cooperative